Civil Service Recruitment : Recruiting the Right Persons the Right Way - van Acker, Wouter (World Bank, Washington, DC, 2019)
Skilled and motivated personnel are arguably the most important determinant of an effective government. How does a government recruit the best and the brightest? This Governance Note examines different approaches to recruiting through career- and position-oriented systems; measuring knowledge versus competencies; screening applicants through written or oral tests; and recruiting junior- and senior-level civil servants. It also compares the advantages and disadvantages of centralized and decentralized recruitment processes. Although this note primarily focuses on civil servants, many of the findings presented here are generalizable to other public employees, such as teachers and health workers.